Analysis of Non Specific Parameters of Simplicia Bloodleaf Plant (Iresine herbstii Hook) During Storage - Putra, Aditya Dwi Permana; Safrina, Devi; Susanti, Dian; Adi, M. Bakti Samsu; Wijaya, Nur Rahmawati; Rukmana, Rizal Maarif (Universitas Muhammadiyah Surakarta, 2024)
Bloodleaf plant, scientifically known as Iresine herbstii Hook, is an ornamental shrub with possible medicinal properties. Storage of simplicia is necessary to guarantee the accessibility of raw materials from I. herbstii. Prolonged storage of simplicia can impact its quality, including many non-specific factors. Indeterminate parameters suggest a relationship between the characteristics of Hook's I. herbstii simplicia during extended storage. This study seeks to ascertain the impact and correlation between the duration of storage of simplicia and the non-specific characteristics of I. herbstii simplicia. Moisture content, extractive value, and ash content were examined in samples with shelf lives of 0 month (IH0), 4 months (IH4), 10 months (IH10), 20 months (IH20), and 32 months (IH32). The acquired data were analyzed using DMRT (Duncan's Multiple Range Test) and MFA (Multiple Factor Analysis). The analysis results indicated that the storage duration impacted all parameters examined except acid-insoluble ash concentration. Prolonged storage of I. herbstii simplicia decreased the concentration of water-soluble and alcohol-soluble extractive value. At the same time, the water content and total ash content increased. The MFA analysis revealed a strong link between non-specific parameters and the duration of storage of I. herbstii simplicia, except for acid-insoluble ash concentration.